IT and productivity: A firm level analysis - Emmanuel Dhyne; Jozef Konings; Jeroen Van den Bosch; Stijn Vanormelingen (National Bank of Belgium, 2018)
Using a novel comprehensive data set of IT investment at the firm level, we find that a firm investing an additional euro in IT increases value added by 1 euro and 38 cents on average. This marginal product of IT investment increases with firm size and varies across sectors. IT explains about 10% of productivity dispersion across firms. While we find substantial returns of IT at the firm level, such returns are much lower at the aggregate level. This is due to underinvestment in IT (IT capital deepening is low) and misallocation of IT investments.
Keywords: D24; L10; O14; O49; 330